RANCANG BANGUN ALAT MONITORING KUALITAS UDARA DI DALAM RUANGAN BERBASIS ARDUINO - Abdillah, Junindo; Iswidodo; Natanael, Ryan (JURNAL TEKNIK INDUSTRI, 2025)
Air pollution on roads and indoors has a bad impact on human health, Since air pollution may lead to a number of illnesses, a device that is useful to track this quality of this air utilizing Arduino, MQ2 sensor, DHT11 sensor and MQ135 sensor as well as the Blynk program, a tool designed to facilitate our ability to see from our cell phones. This test used 3 experiments using lighter gas, perfume and burnt smoke with each value on the resulting gas sensor being different. For pre- trials on lighter gas and perfume when conducting experiments, these two experiments can activate the buzzer with an average value on the mq135 and mq2 sensors of 60-200 ppm. For smoke that is burned, the buzzer is not activated because the gas level received is below 10 ppm.